Accountability of Village Development Based on Huyula Local Culture in Lemito District, Pohuwato Regency - Yanti Aneta; Rustam Tohopi; Yacob Noho nani (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to determine the accountability of Village Fund management in village development carried out by the village government and also the village community based on huyula local cultural values in Lemito District, Pohuwato Regency. The method used in this research is to use a qualitative approach where there are several stages carried out both from the observation stage, interviews and also came to the documentation stage in order to obtain information to support research on the accountability of village funds itself. The results of the study indicate that the form of village government accountability in Lemito District, Pohuwato Regency has implemented the local cultural values of Huyula (Ambu) and has been implemented well by the village government, where in village fund management activities always involve the community and community leaders. There is also the involvement of the BPD (Village Consultative Body), village assistants at the sub-district level and the sub-district government itself. The local cultural values of Huyula (Ambu) have several values, namely the value of unity, the value of deliberation, the value of cooperation, the value of responsibility, and the value of unity.. Huyula or Ambu is carried out with the aim of preserving the values of local wisdom of Gorontalo culture in village development.